STUDY OF CLUSTER FORMATION IN A MODEL OF NANOTECHNOLOGY DEVELOPMENT - BALYAKIN, ARTEM (2012)
MATHEMATICAL MODEL DESCRIBING THE DEVELOPMENT OF SCIENCE (NANOTECHNOLOGY) IN RUSSIAN FEDERATION IS PROPOSED. RESULTS OF NUMERICAL SIMULATIONS ARE PRESENTED AND DISCUSSED IN THE CONTEXT OF SOCIO-ECONOMICAL INTERPRETATION.